A reflection on regulation of strikes in Nigeria. Issue 1 (2nd January 2016) - Abuza, Andrew Ejovwo
Abstract : The Nigerian Government has enacted laws to secure industrial harmony. These laws place restrictions on the exercise of the right of workers to strike. This article reflects on the regulation of strikes in Nigeria. It is the writer's view that governmental efforts to curb incessant strikes in Nigeria have not yielded the desired results as workers under the aegis of their trade unions and federations of trade unions have continued to embark on strike without regard to the statutory restrictions. The writer suggests, among other things, that the government must rise to the challenge of faithfully enforcing these laws.